Isolation And Identification Of Molybdenum-Reducing Cold-Adapted Marine Bacteria Isolated From Bernardo O’Higgins Riquelme Base Station, Antarctica - Darham, Syazani; Gomez Fuentes, Claudio German; Zulkharnain, Azham; Sabri, Suriana; Calisto Ulloa, Nancy Cristina; Ramírez-moreno, Nicolás; Aqlima Ahmad, Siti (My University, 2019)
Molybdenum (Mo) pollution is an emerging problem in some parts of the world. Traces of Mo can be found in the soil and snow even in the most remote part on earth, Antarctica. Bioremediation of Mo using microorganisms has been an up-and-coming alternative in cleaning up Mo from the environment. Mo reduction is a process that transforms sodium molybdate with an oxidation state of 5+ or 6+ to Mo-blue, a less toxic form of the compound. The objectives of this research are to screen, isolate and identify the best cold-adapted Mo-reducing bacterial strain isolated from marine water samples at Bernardo O'Higgins Riquelme Base Station, Antarctica. A total of 11 psychrotolerant strains were seen able to reduce Mo and further studied to determine their taxonomic position using phylogenetic analysis. Based on 16S rRNA identification, the strains were identified as Shewanella sp., Staphylococcus sp. and Marinomonas sp. This study suggests the potential use of the best Mo-reducing cold-adapted bacteria, strain Marinomonas sp. strain AQ5-A9, on the remediating of Mo in the Antarctic region.
Keywords: Antarctic; Molybdenum Pollution; Microbial Remediation; 16S Rrna Identification; Phylogenetic Tree Analysis